Budaya Manajerial Dalam Penerapan Model Organisasi Post Birokrasi di Kantor Imigrasi Serang Propinsi Banten - Arenawati Arenawati; Yeni Widyastuti (Universitas Sultan Ageng Tirtayasa, 2013)
Part of the public bureaucracy is still considered inefficient and ineffective. Formalization is high on bureaucracy often make inefficient bureaucracy and convoluted. Whereas the government as an organization that provides services to the public are required to have higher. To realized responsiveness that there needs to be changes in the organizational model post-bureaucratic organization model in improving government performance. This study aims to determine how the managerial culture and application of post-bureaucratic organization model and how much influence the managerial culture of the post-bureaucratic organizational model application at the Immigration Office Serang. This research is a quantitative survey method. The study population is all employees in the Office of Immigration Serang. The data analysis technique used is the product moment correlation coefficient and the coefficient of determination. From the analysis of known managerial culture in the Immigration Serang is equal to 0.7816, the application of the post-bureaucratic organization of 0.7639. The influence of culture on the application of the managerial post bureaucratic organization of 0.579 or 57.9%, while 42.1% is influenced by other factors. Suggestions in this study need to internalize the organization's values, vision, mission and goals of the organization, formed an informal organization, the development of integrated information systems with relevant agencies, the selection of outstanding employees.